Utilizing in‐vivo feedback for caregiver training of pediatric feeding protocols. Issue 3 (27th February 2020) - Bachmeyer‐Lee, Melanie H.; Kirkwood, Caitlin A.; Sheehan, Connor M.; Gibson, Amanda L.; Shuler, Natalie J.; Keane, Jessica A.
Abstract : Researchers have used multicomponent behavioral skills training packages including written and verbal instructions, modeling, rehearsal, and feedback when teaching caregivers to implement pediatric feeding treatment protocols (e.g., Anderson & McMillan, 2001; Seiverling et al., 2012). Some investigators have shown that fewer behavioral skills training components may be necessary for effective training (e.g., Mueller et al., 2003; Pangborn et al., 2013). We examined the use of in‐vivo feedback following written instructions to train caregivers to implement pediatric feeding treatment protocols using a multiple baseline design across 3 caregiver dyads. Correct implementation of the feeding treatment procedures was low during baseline (written instructions only), increased with only the addition of in‐vivo feedback, and remained high during follow‐up sessions for all caregivers. Results are discussed in terms of clinical implications and caregiver satisfaction.